THE INFLUENCE OF LEARNING SUPERVISION AND PEDAGOGICAL COMPETENCE ON TEACHER PERFORMANCE AT MADRASA ALIYAH SYARIKAT ISLAM AND SMA AL-KHOLILIYAH, PARAKANSALAK DISTRICT, SUKABUMI DISTRICT - Lisna Sujana; Siti Qomariyah (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
Supervision of learning by the madrasa principal has contributed to improving teacher performance. There are also other factors such as pedagogical competence that a teacher must have, which plays a significant role in shaping the performance of a good teacher. It can shape psychological characteristics that can contribute to the level of teacher performance itself. This study aims to explain: (1) the effect of learning supervision on teacher performance (2) The effect of Pedagogic Competence on Teacher Performance and (3) The Effect of Learning Supervision and Pedagogic Competence on Teacher Performance. This study uses a quantitative approach, by collecting data using a questionnaire. The number of respondents in this study was 49 teachers. While to test the hypothesis used path analysis techniques (path analysis) using multiple linear regression analysis techniques. The results of this study indicate that: (1) there is a positive and significant influence between learning supervision and teacher performance 0.014, where p <0,05 which means H0 is rejected and H1 is accepted, (2) There is a positive and significant effect between pedagogic competence and teacher performance with a significant value 0f 0,040, where p <0,05 which means HO is rejected and H1 is accepted, (3) there is a positive and significant effect between learning supervision and pedagogic competence on teacher performance with a significant value of 0.035, where p < 0,05 which means H0 is rejected and H1 is accepted.